PENGARUH PRICE EARNING RATIO (PER), RISIKO KEUANGAN DAN LIKUIDITAS SAHAM TERHADAP RETURN SAHAM PADA PERUSAHAAN SUB SEKTOR PROPERTY & REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - B11110134, Dety Ratna (Jurnal Manajemen Update, 2015)
The aim of this research is to find out the influence of price earning ratio, financial risk and stock liquidity towards stock return. The research carried out by the qualitative and quantitative methods. The data gathered based on secondary data publicated by Indonesian Stock Exchange (BEI). The sample used in this research are of property sub-sector and real estate recorded in Indonesian Stock Exchange (BEI). During the period of 2009-2012, the samples obtained in 4 years period of research from 10 companies amounting to 40 data samples. The result gained from the research showing that stock return influence by the variabel of Price Earning Ratio and Trading Volume Activity, but not by Debt To Equity Ratio. In all together (simultaneously), the stock return influence by Price Earning Ratio, Debt To Equity Ratio and Trading Volume Activity. Â  Key Words: Price Earning Ratio, Debt to Equity Ratio, Trading Volume Activity and stock return